UJI COBA TEKNOLOGI DAUR ULANG CAMPURAN DINGIN DENGAN FOAM BITUMEN PADA JALAN PANTURA JAWA BARAT - Djoko Widajat (Direktorat Bina Teknik Jalan dan Jembatan, 2009)
Technology of recycling can be implemented in the road maintenance program such as road rehabilitation or betterment project. To construct new pavement base course, material for cold mix recycling comes from the existing surface or base pavement layer. An application of foam bitumen binder with addition of active filler, shows an increasing strength of mixture and the impact of water to the mixture can be reduced because of cohesion from fine material particle with the bitumen. Foam bitumen occurred when water and air with a pressure, dispersed into hot bitumen in the expansion chamber, causing foaming of bitumen spontaneously. Fume which occurred during process in contact between water and hot bitumen, trapped in small bubbles which caused bitumen physical characteristic temporary changed. Foam expansion causes asphalt volume increased but in the short time foam reduced and the asphalt volume back to the origin. To make a mixture, as possible aggregate is mixed rapidly with foam bitumen until homogenous mixture obtained. The higher the volume of foam bitumen resulted the higher the bitumen distribution in the mixture. This paper describes about recycling technology with foam bitumen as a binder which has been implemented in Pantura road link. This link is a strategic and economic transportation lane with high volume and heavy traffic loading. The existing pavement has thick bitumen surface course resulted from past overlays. Keywords : recycling, foam bitumen, reclaimed material, filler active.